The efficacy of fetal neural cell aggregates and their combination with fetal liver stromal cells to reduce brain damage after intracerebral hemorrhage in rats - Zolotko, К; Sukach, О; Kompaniets, А (Cell and Organ Transplantology 2021, 9 (1), 22-29, 2021)
Patients with intracerebral hemorrhage have frequent complications and high mortality. There are currently no effective treatments for this disease. We investigated the effect of the use of cryopreserved aggregates of neural cells in combination with fetal liver stromal cells on the reduction of rat brain injury after intracerebral hemorrhage. Methods. Intracerebral hemorrhage (ICH) was modeled in rats by stereotactic administration of 0.2 U of collagenase type IV into the striatum. Neural cell obtained from brain and stromal cells (SCs) – from liver of rat fetuses of 15 dpc. The suspension of neural cell aggregates (NCAs) alone or in combination with fetal liver stromal cells was injected into the lateral ventricle. The level of lipid peroxidation was determined by the thiobarbituric acid test. The degree of brain cells injury after ICH was determined by the activity of lactate dehydrogenase in blood serum. To assess the intensity of adverse factors and the regenerative potential of different variants of cell therapy, the area of the lost striatum in the rat brain and the average distance from the border of the lesion to the nearest neurons were determined. Results. Combined transplantation of NCAs with fetal liver SCs in rats with ICH was found to reduce malonic dialdehyde concentration and lactate dehydrogenase activity more effectively than NCAs alone, indicating inhibition of lipid peroxidation and reduction of cell injury after intracerebral hemorrhage as a result of the addition of SCs. It was shown a significant decrease in the area of lost striatum in both experimental groups. The single administration of NCAs reduced the distance from the lesion border to the nearest neurons the most, indicating the best conditions for survival and/or regeneration of neurons close to the lesion compared to controls. Conclusions. Administration of NCAs, both alone and in combination with fetal liver SCs, reduces the intensity of oxidative stress, preserves the intact striatum tissue, and increases the number of neurons near the brain lesion in intracerebral hemorrhage in rats. The co-transplantation of fetal liver SCs helps to inhibit lipid peroxidation more effectively.
Keywords: intracerebral hemorrhage; neural cells aggregates; fetal liver stromal cells; stereotaxis